Docetaxel-Induced Fatal Interstitial Pneumonitis in a Patient with Castration-Resistant Prostate Cancer - Min, Byung-Dal (The Korean Urological Association, 2012)
A 69-year-old man with castration-resistant prostate cancer (CRPC) received docetaxel and a corticosteroid. After the third cycle of docetaxel administration, he presented with dyspnea, cough, sputum, and fever of 39.2℃. The chest X-ray and chest computed tomography (CT) revealed a diffuse reticulonodular shadow in both lungs, which suggested interstitial pneumonitis. Initially, we used empiric broad-spectrum antibiotics and high-dose corticosteroids. However, his condition progressively became worse and he was transferred to the intensive care unit, intubated, and placed on mechanical ventilation. He died 4 days after hospital admission. Here we report this case of fatal interstitial pneumonitis after treatment with docetaxel for CRPC. We briefly consider docetaxel-induced pneumonitis to make physicians aware of the possibility of pulmonary toxicity so that appropriate treatment can be begun as soon as possible.